The Effect of Principal Transformational Leadership and Motivation on Performance of Teacher in Islamic Elementary School - Yoesoep Edhie Rachmad; Ahmad Mokan; Eulis Sri Rosyidatul Badriyyah; Evi Gusliana; Muhamad Risal Tawil (Journal on Education, 2023)
This study aims to analyze and find: (1) the direct effect of the principal's transformational leadership on teacher performance (2) the direct effect of teacher work motivation on teacher performance (3) the direct effect of the principal's transformational leadership on teacher work motivation, and (4) the indirect effect of transformational leadership of school principals on teacher performance through teacher work motivation. This study uses quantitative methods with data analysis techniques using path analysis. Data collection was carried out using questionnaires, interviews, observation, and documentation. The population in this study was all teachers at SDIT Al-Haraki Depok, totaling 45 teachers. The sampling technique used was random sampling, with sample size referring to the table for determining the number of samples developed by Isaac and Michael with an error rate of 5% and a confidence level of 95%, so that the sample in this study was 40 teachers. The results showed that (1) there was a direct effect of the principal's transformational leadership on teacher performance by 31.5% and (2) there was a direct effect of teacher motivation on teacher performance by 32.8%. (3) There was a 62.5% direct effect of transformational leadership on teacher work motivation; (4) There is a 20.5% indirect effect of transformational leadership on teacher performance through teacher work motivation. Then simultaneously, the effect of the principal's transformational leadership and the teacher's work motivation on teacher performance is 77.6%. In this study, the principal was able to create change and achieve good performance, build a spirit of togetherness and discipline, and motivate teachers and employees to work optimally, which ultimately builds organizational awareness among teachers and employees by developing an attitude of belonging and a sense of responsibility for achieving the highest achievement.